2017
DOI: 10.21608/jappmu.2017.45895
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation for Some Productive and Reproductive Traits in Friesian Cows Raised in Egypt

Abstract: The objective of this study was to estimate the genetic parameters (heritability, and breeding values) as well as the effect of non-genetic factors such as (abdominal arrangement, season and year of calving also interactions between these factors) for some productive and reproductive traits. From the studied traits: total milk yield (TMY, kg), 305 day milk yield (305d-MY, kg), Lactation period (LP, day) as milk production traits, number of services per conception (NSC, services) and age at first calving (AFC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 7 publications
4
5
0
Order By: Relevance
“…In agreement with present results, previous studies concluded significant effects of parity on DO (Faid-Allah, 2015;Rushdi, 2015 andSalem andHammoud, 2016), CI (Sanad, 2016), NSC (Salem andHammoud, 2016 andHassanane, 2017) and AFC (Sanad and Hassanane, 2017). Contradictory to present results, Faid-Allah (2015) and Abosaq et al (2017) indicated that DO increases from the first parity (100.78 and 148.31 d, respectively) to the fifth parity (186.51 and 180.1 d, respectively).…”
Section: Data Presented In Table (supporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with present results, previous studies concluded significant effects of parity on DO (Faid-Allah, 2015;Rushdi, 2015 andSalem andHammoud, 2016), CI (Sanad, 2016), NSC (Salem andHammoud, 2016 andHassanane, 2017) and AFC (Sanad and Hassanane, 2017). Contradictory to present results, Faid-Allah (2015) and Abosaq et al (2017) indicated that DO increases from the first parity (100.78 and 148.31 d, respectively) to the fifth parity (186.51 and 180.1 d, respectively).…”
Section: Data Presented In Table (supporting
confidence: 93%
“…Also, the present mean of CI (377.4 d) was shorter than that of 414.43, 472.0, 433.2 and 427.72 days as presented by Abosaq et al (2017), Farrag et al (2017), Zahed et al (2019) and Habib et al (2020), respectively. Mean of NSC (1.99) was comparable to that values given by Salem and Hammoud (2016)(2.0), Sanad and Hassanane (2017)(1.93) and Abosaq et al (2017)(2.16), while it was lower than the values estimated by Habib et al (2020)(3.0) and Zahed et al (2020)(3.1). Regarding the AFC value (26.97 mo), in present study, it was nearly similar to (27.2 mo) as recorded by Salem and Hammoud (2016).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations